Anglo-American Relations on Film - Cunningham, John (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Any study of British society, particularly after the Second World War, must at some point come to grips with the massive influence of the United States in shaping so much of Britain’s post-war destiny at home and abroad. In many areas of popular culture, dress, music, film, and TV, the USA has often been dominant. In terms of foreign policy British initiatives have become increasingly constrained by the global strategies of the USA. The more recent orientation to the European Union has done little to affect this relationship, particularly as a succession of politicians blow hot or cold on the question of ‘Europe’ or the Trans-Atlantic Alliance’. With the probable exception of the Thatcher years British governments have tended to oscillate between Brussels and Washington, with little coherent policy of their own.